Answer:
h = –xy + r
Explanation:
Given the equation,
:
To solve for h:
Multiply both sides of the equation by y to cancel the fraction on the right-hand side:
![x (y) = ((r-h)/(y)) (y)](https://img.qammunity.org/2022/formulas/mathematics/high-school/8yaxhusf72mipmzvxmc733rqiejmh5oq7h.png)
![xy = r - h](https://img.qammunity.org/2022/formulas/mathematics/high-school/gcmwz16w53l1vuk1hexbal2cohtcxm4wwn.png)
Next, subtract r from both sides:
xy – r = r – r – h
xy – r = – h
Next, divide both sides by -1 to solve for h:
![(xy - r)/(-1) = (-h)/(-1)](https://img.qammunity.org/2022/formulas/mathematics/high-school/l3mad39cvjxyua4qjt90c1rudqt4pegfut.png)
Therefore, the equation for h is:
h = –xy + r